Efficacy of duckweed (Lemna minor Linnneus) integrated in barramundi recirculating aquaculture system (RAS) - Ardiansyah (Curtin University, 2018)
Six experiments were conducted to evaluate nitrogen uptake capacities of duckweed in barramundi recirculating aquaculture systems (RAS). Harvesting duckweed every four days increased the abundance and diversity of both heterotrophic and phosphate-solubilising bacteria, and maximised nitrogen uptake efficiency. A stocking density of less than 18.75 kg m-3 is recommended for culturing barramundi in integrated RAS. The inclusion of fermented duckweeds up to 35% is feasible without adversely affecting growth and physiological parameters of barramundi.